A STUDY ON ATYPICAL CELLS IN HEMATURIA: CYTOLOGICAL FINDINGS AND CLINICAL IMPLICATIONS IN A TERTIARY CARE HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Urine cytology is a simple, rapid, non-invasive, and cost-effective diagnostic tool widely used in the evaluation of urinary tract disorders. It plays an important role in patients presenting with hematuria, aiding in the detection of infections, urolithiasis, and urothelial malignancies. The presence of atypical urothelial cells in urine poses a diagnostic challenge, as it may be associated with both benign and malignant conditions. Aim: To evaluate the cytological features of atypical cells in urine samples from patients with hematuria and to determine their clinical significance. Materials and Methods: This descriptive study was conducted in the Department of Pathology at Sree Mookambika Institute of Medical Sciences from June 2025 to February 2026. A total of 4015 freshly voided urine samples were analyzed. Samples were processed by centrifugation at 1500 rpm for 30 minutes, and smears were prepared from the sediment and stained using routine cytological stains. Detailed microscopic examination was performed to identify atypical and malignant cells. In selected cases, three consecutive urine samples were analyzed to improve diagnostic yield. Statistical analysis was carried out using descriptive and inferential methods, with a p-value